2010
DOI: 10.3109/15376511003746034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butyltin exposures on MAP kinase-dependent transcription regulators in human natural killer cells

Abstract: Natural Killer (NK) cells are a major immune defense mechanism against cancer development and viral infection. The butyltins (BTs), tributyltin (TBT) and dibutyltin (DBT) have been widely used in industrial and other applications and significantly contaminate the environment. Both TBT and DBT have been detected in human blood. These compounds inhibit the lytic and binding function of human NK cells and thus could increase the incidence of cancer and viral infections. Butyltin (BT)-induced loss of NK function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Butyltins, and specifically TBT, an endocrine disruptor, have been found to inhibit the cytotoxic activity of NK cells (269). This effect is accompanied by the activation of the MAPK pathway, which allows the cell to evade growth control (270). This result is confirmed by other studies showing the downregulation by TBT oxide of MAPKs and other proteins, such as matrin-3 and ribonucleotide reductase, subunit RRM2, which are implicated in cell proliferation (274).…”
Section: Cross Talk Between Carcinogens That Affect the Tumor Microenvironment And The Hallmarks Of Cancersupporting
confidence: 52%
“…Butyltins, and specifically TBT, an endocrine disruptor, have been found to inhibit the cytotoxic activity of NK cells (269). This effect is accompanied by the activation of the MAPK pathway, which allows the cell to evade growth control (270). This result is confirmed by other studies showing the downregulation by TBT oxide of MAPKs and other proteins, such as matrin-3 and ribonucleotide reductase, subunit RRM2, which are implicated in cell proliferation (274).…”
Section: Cross Talk Between Carcinogens That Affect the Tumor Microenvironment And The Hallmarks Of Cancersupporting
confidence: 52%
“…TBT also increases the activity of aromatase (estrogen synthetase) (Nakanishi et al, 2002), while DBT has been shown to decrease ligand binding to the glucocorticoid receptor (Gumy et al, 2008). Additionally, TBT increases the phosphorylation and total of levels of the c-Jun component of the AP-1 transcription regulator (Person and Whalen, 2010). Thus, each of these compounds affects the status of transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Coordination polymers, isolated from an appropriate reaction of selected metal centers and multidirectional ligands, aroused an intriguing interest to researchers due to the potential applications as well the fascinating structures they display [1][2][3][4][5][6][7][8][9]. Organotin(IV) carboxylate based complexes and derivatives have been widely investigated because they are a class of compounds affording very interesting topologies, and a variety of structural types such tetramers and oligomeric ladders [10][11][12].…”
Section: Introductionmentioning
confidence: 99%